Subclinical postoperative atrial fibrillation: a randomized trial - Sabbag, Avi; Berkovich, Anat; Raanani, Ehud; Volvovitch, David; McIntyre, William F.; Kassif, Yigal; Kogan, Alexander; Glikson, Michael; Beinart, Roy (Frontiers in Cardiovascular Medicine, 2023)
Background: Postoperative atrial fibrillation (POAF) is the most common complication of cardiac surgery, requiring interventions and prolonging hospital stay. POAF is associated with increased mortality and a higher rate of systemic thrombo-embolism. The rates of recurrent AF, optimal follow-up and management remain unclear. Therefore, we aimed to evaluate the incidence of recurrent atrial fibrillation (AF) events, during long term follow-up in patients presenting with POAF following cardiac surgery. Methods: Patient with POAF and a CHA2DS2-VASc score of ≥2 were randomized in a 2:1 ratio to either implantation of a loop recorder (ILR) or ECG monitoring using periodic Holters. Participants were followed prospectively for 2 years. The primary end point was the occurrence of AF longer than 5 minutes. Results: The final cohort comprised of 22 patients, of whom 14 received an ILR. Over a median follow up of 25.7 (IQR of 24.7 to 44.4) months, 8 patients developed AF, representing a cumulative annualized risk of AF recurrence of 35.7%. There was no difference between ILR (6 participants, 40%) and ECG/Holter (2 participants, 25% P=0.917). All 8 patients with AF recurrence were treated with oral anticoagulation. There were no cases of mortality, stroke or major bleeding. Two patients underwent ILR explantation due to pain at the implantation site. Conclusions: The rate of recurrent AF in patients with POAF after cardiac surgery and a CHA2DS2-VASc score of ≥2 is approximately 1 in 3 when followed systematically. Further research is need to assess the role of ILRs in this population.